1992
DOI: 10.1029/91ja02488
|View full text |Cite
|
Sign up to set email alerts
|

The Nimbus 7 solar total irradiance: A new algorithm for its derivation

Abstract: The Nimbus 7 satellite has measured the solar total irradiance from November 1978 to July 1991 (153 months). These measurements are important both in solar physics and for climate change. To insure that the Nimbus 7 measurements are capturing the true behavior of the Sun, it is essential that the properties of the radiometer and its changes over time be understood. The calibration of the radiometer can be viewed as a process of removing instrumental influences from the raw measurements, leaving the experimente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
78
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(81 citation statements)
references
References 9 publications
2
78
0
Order By: Relevance
“…During this period the only observations available were those of the Nimbus7/ERB (hereafter referred to as ERB) (Hoyt et al 1992) and ERBS/ERBE (hereafter referred to as ERBE) (Lee III et al 1995). These experiments provided TSI observations that met the needs of the Earth Radiation Budget investigations at that time, but were less precise and accurate than the ACRIM experiments that were designed specifically to provide the long term precision and traceability required by climate and solar physics investigations.…”
Section: Introductionmentioning
confidence: 99%
“…During this period the only observations available were those of the Nimbus7/ERB (hereafter referred to as ERB) (Hoyt et al 1992) and ERBS/ERBE (hereafter referred to as ERBE) (Lee III et al 1995). These experiments provided TSI observations that met the needs of the Earth Radiation Budget investigations at that time, but were less precise and accurate than the ACRIM experiments that were designed specifically to provide the long term precision and traceability required by climate and solar physics investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Regular spaceborne measurements of the total solar irradiance (TSI, which is the spectrally integrated solar radiative flux at one au from the Sun) started in 1978 with the launch of the NIMBUS 7 mission (Hoyt et al 1992). They revealed that the TSI varies on multiple timescales (Willson et al 1981;Fröhlich 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since the Maunder Minimum, solar activity has risen steadily to the current Modern Maximum and, according to the 10 Be proxy data, has now reached levels as high as those last seen in the 12th century. Space-based measurements with sufficient precision to identify real changes in solar radiative have been made near the peak of the Modern Maximum but for barely more than one 11-year solar activity cycle (Willson & Hudson 1991;Hoyt et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…With this approach we investigate the effect of various scenarios of depleted bright magnetic elements on the full disk solar emission, estimate the probable reduction of the total solar irradiance during the Maunder Minimum, and use the Goddard Institute for Space Studies (GISS) General Circulation Model (GCM) to calculate the resultant geographical temperature changes that might be expected from this reduction. (Hoyt et al 1992) and (lower panel) the sunspot number.…”
Section: Introductionmentioning
confidence: 99%